Effect of morphine on splanchnic blood flow. - Leaman, D M (1978)
Splanchnic blood flow was measured by the constant infusion of indocyanine green given before and after morphine 0.2 mg/kg (maximum 15 mg) intravenously in 13 patients. Splanchnic blood flow increased from 1012 +/- 98 ml/min to 1200 +/- 118 ml/min after the administration of morphine, a 19 per cent increase (P less than 0.025). Splanchnic vascular resistance decreased from 0.094 +/- 0.010 to 0.081 +/- 0.010 mmHg min/ml, a 16 per cent decrease (P less than 0.001). There was no significant change between baseline and post-morphine values in systemic arterial pressure (92.2 +/- 3.8 and 89.0 +/- 2.9 mmHg), hepatic vein wedge pressure (7.1 +/- 1.0 and 7.8 +/- 0.6 mmHg), or right atrial mean pressure (4.5 +/- 0.6 and 4.3 +/- 0.7 mmHg). This study shows that morphine induced significant splanchnic arteriolar dilatation.